CLASSIFICATION OF CAPABILITY YIELD ON LAPANG TERPADU LABORATORY AGRICULTURE FAKULTY, UNIVERSITY OF LAMPUNG - Iskandar Zulkarnaen (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
Determination of land capabilityof Lapang Terpadu Laboratory FP Unila is very relevant. This researchaims todetermining land capability class on each unit of land in the Lapang Terpadu Laboratory FP Unila. The researchwas conducted from June to October 2013, in the Lapang Terpadu Laboratory FP Unila of approximately 6.784ha area. Thematerials used are a set of secondary datawhich includes climate data, thematicmaps, and chemicalsused for soil analysis in the laboratory. The tools used in this study include: Geographycal Position System(GPS),abney level, ruler, compass, drill ground, ring samples, plastic bags, cameras, laboratory equipment, and stationery(ATK). The studywas conducted by surveymethod. Data physical and chemical properties of the soil obtained byobservation in the field and soil sampling, and then analyzed in the laboratory. Furthermore, the determinationof land capability class is based on inhibiting factors developed by Klingebiel andMontgomery in 1973. LapangTerpadu Laboratory FP Unila has class III, IV, V, and VI, with themain limiting factor for the entire class of landcapability is the steepness of the slopes, except land units 2 is the permeability of the soil rather quickly, and landunits 1 is the threat of flooding. Lapang Terpadu Laboratory FP Unila dominated by land capability class IIIwithland capability class III sub-P4 and III-C,e2, P4 is anarea of 3.989 haor 53.97%, then successivelyfollowed by theclass and sub-class IV land capability -D area of 1,708 ha, or 29.98%, the V-04 area of 0.737 ha or 10.87%, andthe last class VI-E covering an area of 0.351 ha, or 5.17%.Keywords: class slopes, land capability class, inhibiting factors.